2019
DOI: 10.1124/jpet.119.262048
|View full text |Cite
|
Sign up to set email alerts
|

Impaired Endothelium-Dependent Hyperpolarization Underlies Endothelial Dysfunction during Early Metabolic Challenge: Increased ROS Generation and Possible Interference with NO Function

Abstract: Endothelial dysfunction is a hallmark of diabetic vasculopathies. Although hyperglycemia is believed to be the culprit causing endothelial damage, the mechanism underlying early endothelial insult in prediabetes remains obscure. We used a nonobese high-calorie (HC)-fed rat model with hyperinsulinemia, hypercholesterolemia, and delayed development of hyperglycemia to unravel this mechanism. Compared with aortic rings from control rats, HC-fed rat rings displayed attenuated acetylcholinemediated relaxation. Whil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 100 publications
(100 reference statements)
2
19
0
Order By: Relevance
“…Out of the STZ-injected rats developing T2D, those receiving insulin injections (INS) rats consumed more calories than the average consumption of T2D rats for 2-wk duration of insulin treatment (data not shown). Similar to our previous studies (2,3,20), MHC feeding did not result in a weight difference compared with control rats; however, rats developing T2D after STZ injection appeared to lose weight starting at week 9 (Fig. 1B).…”
Section: Resultssupporting
confidence: 89%
See 1 more Smart Citation
“…Out of the STZ-injected rats developing T2D, those receiving insulin injections (INS) rats consumed more calories than the average consumption of T2D rats for 2-wk duration of insulin treatment (data not shown). Similar to our previous studies (2,3,20), MHC feeding did not result in a weight difference compared with control rats; however, rats developing T2D after STZ injection appeared to lose weight starting at week 9 (Fig. 1B).…”
Section: Resultssupporting
confidence: 89%
“…As such, we hypothesize that the major mediator of development of CAN in T2D with progressive metabolic deterioration, from insulin resistance to hyperglycemia, is the extent and localization of inflammation. For this purpose, we used our previously developed rat model of early metabolic challenge (2,3,20) and extended the investigation by induction of T2D using sequential injections of lowdose streptozotocin (STZ). We also investigated the effect of metformin, pioglitazone, insulin, or their combinations on the inflammatory and autonomic changes at this late stage.…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, cereal grains such as rice have attracted much scientific attention [1] because they contain phenolic compounds such as quercetin, ferulic acid, and salicylic acid [2] which have strong antioxidant abilities [3]. Over the years, oxidative stress has been shown to play a key role in the pathogenesis of hypertension [4,5] since reactive oxygen species can cause endothelial dysfunction [6] leading to arterial stiffness in humans [7,8]. One popular physiological mechanism of hypertension is the renin-aldosterone-angiotensin system (RAAS) [9].…”
Section: Introductionmentioning
confidence: 99%
“…In fact, obese patients with insulin resistance had systemic arterial dysfunction concurrent with high M1 ATMs and TNFα mRNA in SAT and elevated serum C reactive protein (CRP), indicating a proinflammatory state (Apovian et al, 2008). Interestingly, recent studies on a prediabetic rat model showed that mildly increased caloric intake led to clear cardiovascular manifestations even in absence of overt hyperglycemia, increased body weight, or high blood pressure (Al-Assi et al, 2018;Alaaeddine et al, 2019;Elkhatib et al, 2019). Significantly, the observed endothelial dysfunction and CAN were linked to localized PVAT inflammation with neither inflammatory changes in other adipose pool nor systemic involvement (Al-Assi et al, 2018;Alaaeddine et al, 2019;Elkhatib et al, 2019).…”
Section: Adipose Tissue and Cardiometabolic Syndromementioning
confidence: 99%
“…Interestingly, recent studies on a prediabetic rat model showed that mildly increased caloric intake led to clear cardiovascular manifestations even in absence of overt hyperglycemia, increased body weight, or high blood pressure (Al-Assi et al, 2018;Alaaeddine et al, 2019;Elkhatib et al, 2019). Significantly, the observed endothelial dysfunction and CAN were linked to localized PVAT inflammation with neither inflammatory changes in other adipose pool nor systemic involvement (Al-Assi et al, 2018;Alaaeddine et al, 2019;Elkhatib et al, 2019). This early PVAT involvement in the course of metabolic disease is of particular relevance given the close anatomical proximity between PVAT and the cardiovascular tissue.…”
Section: Adipose Tissue and Cardiometabolic Syndromementioning
confidence: 99%